HUBUNGAN KEBISINGAN DENGAN STRES KERJA PADA PERKERJA BAGIAN PRODUKSI DI PT MITRA BUMI - Yusmardiansyah Yusmardiansyah Yusmardiansyah; Ghania Zhara Zhara (Universitas Pahlawan, 2019)
Noise is a physical environmental factor that affects work health and is one of the factors that can cause additional burdens for work. The purpose of this study was to determine the relationship of noise to work stress in production section workers at PT Mitra Bumi in 2019. Stress on workers can be caused by factors that are less comfortable working environment, workload that is too large, low education and wage income and income wages for meet increasing needs so workers tend to cause stress. This type of research is analytic with cross sectional design. The population in this study were all workers in the production section at PT. Mitra Bumi numbered 43 people with a sample of 43 people with the sampling technique used was total sampling. Data collection tools in this study used a questionnaire. The data analysis in this study is univariate and bivariate. The results of this study found that there is a relationship between noise and work stress at PT. Mitra Bumi in 2019 with a p value of 0.001. It is expected that companies can make noise control efforts in the workplace by providing ear protection to workers and conducting periodic health checks on workers such as hearing examinations, providing health promotion, socialization and training in order to increase workers' knowledge about the importance of using ear protection equipment for workers.